4-Formylazetidin-2-ones, synthon for the synthesis of (2R,3S) and (2S,3R)-3-amino-2-hydroxydecanoic acid (AHDA) - Shirode, N. M.; Deshmukh, A. R. A. S. (Tetrahedron, 2006)
An efficient synthesis of 3-amino-2-hydroxydecanoic acid (AHDA), a nonproteinogenic amino acid, using enantiopure 3-benzyloxy-4-formylazetidin-2-one as a building block is described. Both the enantiomers of AHDA have been synthesized from the corresponding enantiomer of 3-benzyloxy-4-formylazetidin-2-one in good yield and optical purity. (c) 2006 Published by Elsevier Ltd.
Keywords: Amino acids; azetidin-2-ones; Staudinger reaction; stereoselective synthesis; Wittig reaction